Genome-Wide Analysis Reveals Selective Modulation of microRNAs and mRNAs by Histone Deacetylase Inhibitor in B Cells Induced to Undergo Class-Switch DNA Recombination and Plasma Cell Differentiation - Shen, Tian; Sanchez, Helia N.; Zan, Hong; Casali, Paolo (Frontiers in Immunology, 2015)
As we have suggested, epigenetic factors, such as microRNAs (miRNAs), can interact with genetic programs to regulate B cell functions, thereby informing antibody and autoantibody responses. We have shown that histone deacetylase inhibitors (HDI) inhibit the differentiation events critical to the maturation of the antibody response: class-switch DNA recombination (CSR), somatic hypermutation (SHM) and plasma cell differentiation, by modulating intrinsic B cell mechanisms. HDI repress the expression of AID and Blimp-1, which are critical for CSR/SHM and plasma cell differentiation, respectively, in mouse and human B cells by upregulating selected miRNAs that silenced AICDA/Aicda and PRDM1/Prdm1 mRNAs, as demonstrated by multiple qRT-PCRs (J. Immunol. 193:5933-5950, 2014). To further define the selectivity of HDI-mediated modulation of miRNA and gene expression, we performed genome-wide miRNA-Seq and mRNA-Seq analysis in B cells stimulated by LPS plus IL-4 and treated with HDI or nil. Consistent with what we have shown using qRT-PCR, these HDI-treated B cells displayed reduced expression of Aicda and Prdm1, and increased expression of miR-155, miR-181b and miR-361, which target Aicda, and miR-23b, miR-30a and miR-125b, which target Prdm1. In B cells induced to undergo CSR and plasma cell differentiation, about 23% of over 22,000 mRNAs analyzed were expressed at a significantly high copy number (more than 20 copies/cell). Only 18 (0.36%) of these highly expressed mRNAs, including Aicda, Prdm1 and Xbp1, were downregulated by HDI by 50% or more. Further, only 16 (0.30%) of the highly expressed mRNAs were upregulated (more than twofold) by HDI. The selectivity of HDI-mediated modulation of gene expression was emphasized by unchanged expression of the genes that are involved in regulation, targeting or DNA repair processes of CSR, as well as unchanged expression of the genes encoding epigenetic regulators and factors that are important for cell signaling or apoptosis. Our findings indicate that, in B cells induced to undergo CSR and plasma cell differentiation, HDI modulate selected miRNAs and mRNAs, possibly as a result of HDACs existing in unique contexts of HDAC/co-factor complexes, as occurring in B lymphocytes, particularly when in an activated state.